Overproduction and crystallization of FokI restriction endonuclease. - Kita, K (1989)
To overproduce FokI endonuclease (R.FokI) in an Escherichia coli system, the coding region of R.FokI predicted from the nucleotide sequence was generated from the FokI operon and joined to the tac promoter of an expression vector, pKK223-3. By introduction of the plasmid into E. coli UT481 cells expressing the FokI methylase gene, the R.FokI activity was overproduced about 30-fold, from which R.FokI was purified in amounts sufficient for crystallization. The removal of a stem-loop structure immediately upstream of the R.FokI coding region was essential for overproduction.